An application of quality function deployment to improve service quality in a cellular mobile telephone company - Macatangay, Leah Alvino (1999)
The thesis sought to design the service quality rendered by a cellular mobile telephone company using Quality Function Deployment, a structured methodology, in order to measure and improve service quality. A customer Satisfaction/Quality of Service Enhancement Survey was conducted among subscribers of three cellular phone companies in order to derive the importance they gave to previously identified customer wants and needs, and to assess their present level of satisfaction with the service they currently receive from their service provider. The respondents of Company A rated "Always have a signal" the most important need, followed by "Accurate billing", "Can reach many places", "Pay for calls made", "Clear and continuous reception", and so on. For Company A's cellular service, a design model called the House of Quality was constructed. The results of the survey served as inputs to the first four columns of the Planning Matrix of the House of Quality. The rest of the columns, as well as the other parts of the House of Quality, such as Priorities, Competitive Benchmarks, and Targets were filled in with computed values as well as decisions made by the development team.
Simultaneously, apart from QFD, statistical tests were performed: Analysis of Variance tests were performed to verify the significance of the differences in the means of importance ratings and those of the satisfaction ratings of the 18 variables. Duncan Multiple Range tests were conducted to identify which relationships among the three companies were significant. Factor Analysis was used to identify five common underlying factors among the importance variables and among the satisfaction variables. The Importance vs. Satisfaction Grid was constructed to identify the variables that "need attention": Coverage and Customer Service.
Following the QFD methodology and the ranked Priorities, and supported by the results of the Factor Analysis, Importance vs. Satisfaction Grid, and Customer Complaints, further deployment was carried out in four main areas of investigation and improvement: Billing/Customer Care System, Customer Service, Use of QFD, and Others
The acquisition of a Billing/Customer Care software program was recommended, which featured Process Control Plans for four main processes: Billing and Collection, Customer Service, Market Intelligence, and Churn Management. Customer Services recommendations included the increase in number of CSRs, the introduction of quality circles, and the review of performance measures. Another recommendation was the use of QFD on a regular basis, as a way of concretizing Company A's service mission. Finally, various recommendations bases on common complaints included greater use of the Internet, education of the general public on the features of cell phone service, and the re-design of the company's Instruction Manual and quarterly newsletters.
It can be thus concluded that QFD is a very applicable and effective tool for design that was successfully used on the cellular phone service of Company A, in order to measure service quality, to identify areas for improvement, and to make recommendations in these identified areas.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Diliman.
Keywords: Cellular radio -- Philippines; Quality function deployment; Telecommunication systems -- Philippines